Hemingway's Spain : Imagining the Spanish World - Cirino, Mark, 1971-; Eby, Carl P. (Book collections on Project MUSE., 2015)
Ernest Hemingway famously called Spain the country that I loved more than any other except my own, and his forty-year love affair with it provided an inspiration and setting for major works from each decade of his career: The Sun Also Rises, Death in the Afternoon, For Whom the Bell Tolls, The Dangerous Summer, and The Garden of Eden; his only full-length play, The Fifth Column; the Civil War documentary The Spanish Earth; and some of his finest short fiction, including Hills Like White Elephants and A Clean, Well-Lighted Place. In Hemingway's Spain, Carl P. Eby and Mark Cirino collect thirteen penetrating and innovative essays by scholars of different nationalities, generations, and perspectives who explore Hemingway's writing about Spain and his relationship to Spanish culture and ask us in a myriad of ways to rethink how Hemingway imagined Spain whether through a modernist mythologization of the Spanish soil, his fascination with the bullfight, his interrogation of the relationship between travel and tourism, his involvement with Spanish politics, his dialog with Spanish writers, or his appreciation of the subtleties of Spanish values. In addition to fresh critical responses to some of Hemingway's most famous novels and stories, a particular strength of Hemingway's Spain is its consideration of neglected works, such as Hemingway's Spanish Civil War stories and The Dangerous Summer. The collection is noteworthy for its attention to how Hemingway's post World War II fiction revisits and re-imagines his earlier Spanish works, and it brings new light both to Hemingway's Spanish Civil War politics and his reception in Spain during the Franco years. Hemingway's lifelong engagement with Spain is central to understanding and appreciating his work, and Hemingway's Spain is an indispensable exploration of Hemingway's home away from home.